Analisis Angkutan Umum Bus Trans-Mamminasata Koridor III Berdasarkan Biaya Operasional Kendaraan - Develson Liwan; Benyamin Tanan; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2023)
One of the public transportation that uses a fare system is the Trans-Mamminasata Bus. The regional government determines the amount of the fare for a vehicle by setting an upper and lower limit which is adjusted to the amount of vehicle operating costs (BOK), thus it is hoped that the fare charged to passengers is not burdensome or in accordance with applicable regulations. The aim of this research is to find out the load factor of the Trans-Mamminasata Bus, what the Vehicle Operational Costs (BOK) of the Trans-Mamminasata Bus are and what the appropriate fare is based on vehicle operational costs. The data used in this research is secondary data obtained from related agencies and primary data obtained from load factors and interviews. The BOK analysis method used is LAPI ITB 1997. The results obtained are that the average load factor obtained is 0.074%, the operational cost of the Trans-Mamminasata bus vehicle is IDR 8,822.68/km and the tabulated fare determination is obtained from the load. the average factor is the basic rate of IDR 5,961.27; fare IDR 129,061.60 per passenger and standard load factor 70% basic fare IDR 330.19; and the fare is IDR 13,643.74 per passenger. Meanwhile, for 100% load factor tariff, the basic tariff is IDR 441,134; and the fare is IDR 9,550.65 per passenger